Enhancing Photovoltaic-Thermoelectric Generator (PV-TEG) system performance via mathematical modeling and advanced thermal interface material: An emphasis on Pyrolytic graphite Sheet (PGS) - Mahmoud AL Shurafa S.; Basim Ismail F.; Kazem H.A.; Ee Sann T.; Abdel Hameed Almajali T. (Elsevier Ltd, 2025)
PV-TEG systems utilize waste heat by using TEGs under PV panels. TEGs improve the efficiency of PV and generates more energy. However, rough metal surfaces at contact points reduce the system's thermal efficiency and create air gaps. This paper employs a mathematical model based on principles of thermal resistances and energy conservation. The proposed model is built using MATLAB R2020a. The paper assessed the effectiveness of a Pyrolytic Graphite Sheet (PGS) as a Thermal Interface Material (TIM) in PV-TEG systems and three cooling approaches. The investigation explores two configurations (parallel and bent) of PGS and five TIM materials. The results indicate that bent PGS is the most effective. It lowers the temperature of the PV panels to 18.99 ?, 19.95 ?, and 20.74 ?. As a result, the power increased to 0.606 W, 0.639 W, and 0.667 W. Additionally, the efficiency improves to 1.66 %, 1.75 %, and 1.82 % with natural air, forced air, and forced water cooling, respectively. The results show that PGS can improve PV-TEG system performance and solve thermal issues with metal surfaces and air gaps. ? 2024 International Solar Energy Society